ANALYSIS OF POSSIBILITIES FOR INTEGRATING THE TRANSPORT SYSTEM OF UKRAINE INTO THE EUROPEAN TRANSPORT NETWORK - Nesterenko, H. I.; Muzykin, M. I.; Strelko, O. H.; Bibik, S. I.; Aleksieieva, A. O. (Systems and Technologies, 2023)
This article is devoted to the analysis of transport networks of such European countries as Ukraine, Hungary, and Romania. The article provides an analysis of the peculiarities in the movement organization in these countries. The transport systems of these countries were researched since during the war the issue of the interaction of the automobile transport networks exactly in these countries became particularly relevant. After all, there are incredibly long queues at the checkpoints in Poland because of strikes by Polish customs officers. And, therefore, the routes through Romania and Hungary are the most realistic both during the export of goods from Ukraine and to import humanitarian goods. The joint use of Europe's integrated systems is a necessary component in the organization of the effective operation of road transport, as it ensures increased efficiency in the use of the motor vehicle fleet and personnel; reduction of costs for maintenance, fuel, lubricants due to optimization of routes and reduction of non-productive vehicle mileage; reduction of the need to expand the motor vehicle fleet; clearer prospective planning of work based on objective information about the real mileage of each vehicle unit and reduction of losses related to repairs and expansion of the range of services and prompt response to requests. It is advisable to conduct further research in the direction of adapting the use of augmented reality technology in the driver's navigation systems.